Smartphone Use and Academic Performance: First Evidence from Longitudinal Data - Simon Amez; Sunčica Vujić; Lieven De Marez; Stijn Baert (Global Labor Organization (GLO), 2019)
To study the causal impact of smartphone use on academic performance, we collected—for the first time worldwide—longitudinal data on students' smartphone use and educational performance. For three consecutive years we surveyed all students attending classes in eleven different study programmes at two Belgian universities on general smartphone use and other drivers of academic achievement. These survey data were merged with the exam scores of these students. We analysed the resulting data by means of panel data random effects estimation controlling for unobserved individual characteristics. A one standard deviation increase in overall smartphone use results in a decrease of 0.349 points (out of 20) and a decrease of 2.616 percentage points in the fraction of exams passed.
Keywords: I23; J24; 330; smartphone use; academic performance; longitudinal data; causality